Pengaruh Brand Ambassador Bangtan Sonyeondan Terhadap Brand Image E-Commerce Tokopedia (Studi Kasus Mahasiswa Universitas Batanghari) - Mappedeceng, Riko; Tamizi, Ahmad; Dinarti, Inggit (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims first to analyze the description of BTS Brand Ambassadors towards Tokopedia Brand Images among Unbari Students. And the second is to find out the strategy for determining Brand Ambassadors to build a Brand Image In this research the author will analyze the data obtained descriptively qualitatively. The data source is Tokopedia users at Batanghari University who are research respondents. This questionnaire is in the form of closed questions where alternative answers are available from 1-5. The data collection methods used are Field Research and Library Research. The object of this research is Tokopedia which operates in the e-commerce industry. Electronic Commerce or e-commerce is all buying and selling activities or transactions carried out using electronic media (the internet). There are several examples of e-commerce that are often used in Indonesia. These include Shopee, Bukalapak, or Tokopedia. Several examples of e-commerce have now become a business area for business people. Based on a simple linear regression test, it is known that the Brand Ambassador value is 0.563, which means that product quality has a positive value for Brand Image. Based on the t test, it is known that there is a significant influence between the Brand Ambassador and the Tokopedia Brand Image, proven by the t test t count > t table (10.985> 1.66088), meaning that Ho is rejected and Hi is accepted so it can be stated that the Brand Ambassador can have a significant influence on the Brand Image. Every time there is an increase in Brand Ambassador by 1%, the Brand Image on Tokopedia will increase by 56.3%. Conclusion of research is From the results of the Likert scale, the influence of Brand Ambassadors on Tokopedia's Brand Image with an average score of 383 means that consumers assess Brand Ambassadors as having a good influence. Furthermore, the Brand Image of consumers using Tokopedia with an average score of 366 means that the Brand Image indicator is good.